Microallelotyping defines novel regions of loss of heterozygosity in uterine leiomyomas - Canevari, R. D.; Pontes, Anaglória [UNESP]; Rogatto, Silvia Regina [UNESP] (Wiley-Blackwell, 2005)
Uterine leiomyomas are extremely common, benign, smooth muscle tumors that represent a significant public health problem. Although there have been few molecular studies of uterine leiomyomas, most of them have reported a very low frequency of loss of heterozygosity (LOH) in different regions of the genome. The detection of LOH has been used to identify genomic regions that harbor tumor suppressor genes and to characterize different tumor types. We have used a set of 15 microsatellite polymorphism markers to examine the frequency of allele loss in a panel of 64 human uterine leiomyomas matched to normal DNAs. The markers were chosen from regions involved in losses identified by comparative genomic hybridization in a subset of uterine leiomyomas described in a previous report. DNA from tumors and normal tissue was amplified by the polymerase chain reaction and subsequently analyzed using an ABI Prism 377 DNA automated sequencer. The frequency of LOH observed was low, except for the markers D15S87 (15q26.3), D7S493 (7p15.3), and D7S517 (7p22.2). No changes in microsatellite size were detected in our samples. These results provide useful clues for identifying putative tumor suppressor genes associated with a subset of uterine leiomyomas. (C) 2004 Wiley-Liss, Inc.
Keywords: microallelotyping; loss of heterozygosity; uterine leiomyomas